Some Third Order Methods for Solving Nonlinear Equations - Jnawali, Jivandhar (Journal of the Institute of Engineering, 2018)
There are several third order numerical methods having same efficiency index appeared in literature for solving nonlinear equations of a single variable. Practically, if we apply these methods in different nonlinear equations, we can observe that all methods are not performed equally for given nonlinear equations. The main objective of this paper is to show through numerical experiment that the performance of some third order methods having the same efficiency index does not perform equally for particular nonlinear equation. For the numerical comparison, we use Matlab software. 2010 AMS Subject Classification: 65H05 Journal of the Institute of Engineering, 2017, 13(1): 169-174